The Flourishing Women: - Mu'minin, Nashrul (Jurnal Perempuan dan Anak, 2024)
Progressive women is a term that refers to women who have succeeded in achieving success in various fields, such as education, career, and social life. The keywords in the concept of progressive women are "success" and "various fields". Progressive women have proven that they are able to pursue their dreams and achieve their life goals, which can be an inspiration for many people, especially for other women who want to pursue their dreams and achieve their life goals as well. However, progressive women also often face various challenges and obstacles in achieving success.